Latihan Zig-Zag Run dan Shuttle Run untuk Meningkatkan Kelincahan Atlet Stepa Basketball Madiun - Aziz Herdiansyah; Fatkur Rohman Kafrawi; Himawan Wismanadi; Dita Yuliastrid (Mutiara Pendidikan dan Olahraga, 2026)
Basketball requires mastery of basic technical skills and supportive physical conditions, including agility, which plays a crucial role in dribbling control and game effectiveness. In the extracurricular activities of Stepa Basketball Madiun, agility training has not been applied systematically, necessitating effective training methods to enhance athletes’ abilities. This study aimed to examine the effects of zig-zag run and shuttle run exercises on athletes’ agility and to compare the effectiveness of both exercises. A numerical methodology utilizing a pre-experimental One-Group Pretest–Posttest framework was implemented. The participants comprised 12 athletes between 13 and 15 years of age, who were allocated into two intervention groups. Data were collected using the Edgren Side Step Test before and after six weeks of training, conducted three times per week, and analyzed using t-tests. The results indicated that both exercises significantly improved athletes’ agility, with shuttle run showing a slightly greater improvement than zig-zag run. These findings reinforce the concept that agility can be enhanced through structured training emphasizing directional changes and speed, and provide practical implications for coaches to integrate shuttle run and zig-zag run exercises in training programs to optimize athletes’ performance.